Effects of tetrahydroxy stilbene glycoside derivatives on free radical damage and apoptosis in APP695V717I transgenic mice - Qian, Jun; Li, Yun; Wang, Yanyun; Ye, Qunying; Luo, Hongbo (Redox report : communications in free radical research, 2023)
Mitochondrial dysfunction leading to overproduction of oxygen free radicals is an important event in the development of Alzheimer's disease. Tetrahydroxy stilbene glycoside (TSG) is one of the main effective components of Polygonum multiflorum and has a certain free radical scavenging effect. We synthesized tetrahydroxy stilbene glycoside derivatives (Mito-TSGs) that can cross the mitochondrial membrane and may provide effective protection against Alzheimer's disease. This experiment investigates the protective mechanism of tetrahydroxy stilbene glycoside derivatives against mitochondrial free radical damage and apoptosis in APP695V717I transgenic model mice. The experimental subjects were healthy 3-month-old APP695V717I transgenic model mice, while C57BL/6J mice of the same age and genetic background served as controls. The results demonstrated that the tetrahydroxy stilbene glycoside derivatives significantly improved mouse behavioral performance. It also led to a decrease in the levels of H2O2, NO, MDA, and LD, along with an increase in LDH activity and in the antioxidant enzyme activity of SOD, CAT, and GSH-Px. Moreover, it elevated the mitochondrial membrane potential, decreased the gene and protein expression of Caspase-3 and Bax, and increased the gene and protein expression of Bcl-2. Notably, the effectiveness of tetrahydroxy stilbene glycoside derivatives was superior to that of traditional tetrahydroxy stilbene glycoside.Mitochondrial dysfunction leading to overproduction of oxygen free radicals is an important event in the development of Alzheimer's disease. Tetrahydroxy stilbene glycoside (TSG) is one of the main effective components of Polygonum multiflorum and has a certain free radical scavenging effect. We synthesized tetrahydroxy stilbene glycoside derivatives (Mito-TSGs) that can cross the mitochondrial membrane and may provide effective protection against Alzheimer's disease. This experiment investigates the protective mechanism of tetrahydroxy stilbene glycoside derivatives against mitochondrial free radical damage and apoptosis in APP695V717I transgenic model mice. The experimental subjects were healthy 3-month-old APP695V717I transgenic model mice, while C57BL/6J mice of the same age and genetic background served as controls. The results demonstrated that the tetrahydroxy stilbene glycoside derivatives significantly improved mouse behavioral performance. It also led to a decrease in the levels of H2O2, NO, MDA, and LD, along with an increase in LDH activity and in the antioxidant enzyme activity of SOD, CAT, and GSH-Px. Moreover, it elevated the mitochondrial membrane potential, decreased the gene and protein expression of Caspase-3 and Bax, and increased the gene and protein expression of Bcl-2. Notably, the effectiveness of tetrahydroxy stilbene glycoside derivatives was superior to that of traditional tetrahydroxy stilbene glycoside.